Phytocannabinoid effect on alpha-synuclein aggregation - Velez, João Serra (2022)
Parkinson’s disease is a fast-growing disease in terms of prevalence, especially in the last generation. The symptoms of PD are usually associated with impairments in motor skills. Lewy bodies are a PD feature widely accepted by the scientific community. The Lewy bodies are mainly composed by α-synuclein (α-syn). According to the literature, the formation of α-syn oligomers due to folding changes forming β-sheets, which are seen in amyloid fibrils structure is the currently accepted hypothesis regarding the rise of the Lewy pathologies and their neurodegenerative roles. Cannabis is used by Parkinson´s Disease patients worldwide to reduce symptoms. Recent studies suggest that the effects of phytocannabinoids are mediated by CB1 and/or CB2 receptors. The present study aimed to understand the interactions between α-synuclein and cannabidiol, by studying the behaviour of α-synuclein in solution when exposed to this phytocannabinoid. After α-synuclein purification, the protein was incubated, with Cannabidiol (CBD) and its oligomeric profile, aggregation rate and secondary structure was assessed by gel exclusion chromatography, ThT fluorescence spectroscopy and circular dichroism. The results from the size-exclusion chromatography reveal an equilibrium between dimer and tetramer, with a higher increase of the dimer in the CBD sample. Regarding the circular dichroism, the percentage of random coil decreased in both samples. The ThT analysis led to the conclusion that there was no aggregation of α-synuclein. At low protein concentration the size-exclusion chromatography revealed a dynamic equilibrium between the dimeric and monomeric species, which in turn change to other monomeric form, appearing in the chromatogram, towards the end of the experiment.